An Experimental Approach to Assessing the Perceived Value of Personal and Social Responsibility. Issue 3 (2nd July 2016) - Daugherty, Timothy K.
Abstract: Personal and social responsibility (PSR), one of four essential learning outcomes identified by the Liberal Education and America's Promise (LEAP) Report (AAC&U, 2007), was rated as "very" or "extremely" important by 88% of the participants in the study. To supplement the expected results from the traditional survey methods that assess the perceived value of PSR, this study provided additional experimental evidence that students were sensitive to, and highly valued, the markers of achieving PSR. Participants were randomly assigned to examine one résumé in a 3 (GPA) × 2 (PSR) design. Beyond and independent of the effect of academic achievement, PSR positively influenced hiring decisions, salary recommendations, and performance expectations.